1991
DOI: 10.1128/jb.173.21.6811-6819.1991
|View full text |Cite
|
Sign up to set email alerts
|

Molecular cloning of a Pseudomonas paucimobilis gene encoding a 17-kilodalton polypeptide that eliminates HCl molecules from gamma-hexachlorocyclohexane

Abstract: Pseudomonas paucimobilis UT26 is capable of growing on 'y-hexachlorocyclohexane (,y-HCH). A genomic library of P. paucimobilis UT26 was constructed in Pseudomonas putida by using the broad-host-range cosmid vector pKS13. After 2,300 clones were screened by gas chromatography, 3 clones showing y-HCH degradation were detected. A 5-kb fragment from one of the cosmid clones was subcloned into pUC118, and subsequent deletion and gas chromatography-mass spectrometry analyses revealed that a fragment of ca. 500 bp wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
144
0
1

Year Published

1993
1993
2022
2022

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 155 publications
(149 citation statements)
references
References 44 publications
4
144
0
1
Order By: Relevance
“…All the HCH catabolic genes (called lin genes) involved in the degradation of γ-HCH isomer have been identifi ed in S. japonicum UT26 3,4 . The primary enzyme in γ-HCH degradation is HCH dehydrochlorinase encoded by linA 5 . The remaining genes of the γ-HCH degradative pathway are linB 6 , linC 7 , linD 8 , linE/linEb 9,10 , linF 10 , linGH 4 and linJ 4 encoding haloalkane dehalogenase, dehydrogenase, reductive dechlorinase, ring-cleavage oxygenase, maleylacetate reductase, acyl-CoA transferase and thiolase, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…All the HCH catabolic genes (called lin genes) involved in the degradation of γ-HCH isomer have been identifi ed in S. japonicum UT26 3,4 . The primary enzyme in γ-HCH degradation is HCH dehydrochlorinase encoded by linA 5 . The remaining genes of the γ-HCH degradative pathway are linB 6 , linC 7 , linD 8 , linE/linEb 9,10 , linF 10 , linGH 4 and linJ 4 encoding haloalkane dehalogenase, dehydrogenase, reductive dechlorinase, ring-cleavage oxygenase, maleylacetate reductase, acyl-CoA transferase and thiolase, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…2), as expected. 3) The substrate specificity of LinA was examined. It was suggested that the activity of LinA would be very specific to y-HCH and its metabolic intermediate y-PCCH.…”
mentioning
confidence: 99%
“…A bacterial strain, Sphingomonas paucimobilis UT26 (formerly known as Pseudomonas paucimobilis UT26), was found to grow on hexachlorocyclohexane (HCH, or lindane) as a sole source of carbon Imai, 1989). Subsequently, the enzymes involved in HCH degradation had been purified (Nagata, 1993a) and the relevant genes in the metabolic pathway were cloned and sequenced (Imai, 1991;Nagata, 1993bNagata, , 1994Miyauchi, 1998).…”
Section: Introductionmentioning
confidence: 99%